2019
DOI: 10.1002/14651858.cd004705.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical risk assessment as an aid for smoking cessation

Abstract: We did not find evidence that giving smokers feedback on their smoking exposure, their genetic risk of smoking-related disease, or the e ects of smoking on their body helps them quit smoking. The most promising results were for giving people feedback on the harm smoking does to their bodies. The studies did not report on harms or side e ects of providing feedback. However, given the nature of the measurements (lung or blood tests), we would expect the risk of harms to be low. Certainty of evidence Because of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 125 publications
2
28
0
1
Order By: Relevance
“…The evidence about the effect of spirometry as a motivational strategy to quit smoking is limited and controversial. 15 Our findings in this pragmatic clinical trial confirmed that patients who received brief advice plus detailed spirometry information doubled prolonged abstinence rates, compared with brief advice alone, in 12-month follow-up (HR 1.98 (95% CI 1.29 to 3.04)). Success was also more likely in participants at advanced stage of the change process (preparation or action), and in those who accepted an intensive-motivational intervention and/or use smoking cessation pharmacotherapy.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The evidence about the effect of spirometry as a motivational strategy to quit smoking is limited and controversial. 15 Our findings in this pragmatic clinical trial confirmed that patients who received brief advice plus detailed spirometry information doubled prolonged abstinence rates, compared with brief advice alone, in 12-month follow-up (HR 1.98 (95% CI 1.29 to 3.04)). Success was also more likely in participants at advanced stage of the change process (preparation or action), and in those who accepted an intensive-motivational intervention and/or use smoking cessation pharmacotherapy.…”
Section: Discussionsupporting
confidence: 76%
“… 25 In a recent systematic review that examined the effects of spirometry on smoking cessation, only one study (of five total) indicated efficacy of spirometry feedback and linked lung age to increased smoking quit rates. 15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations